1974
DOI: 10.1128/am.27.3.513-516.1974
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Disposition of 2, 4, 6-Trinitrotoluene

Abstract: Three pseudomonas-like organisms have been shown to metabolically oxidize 2, 4, 6-trinitrotoluene (TNT). Capability for this oxidative dissimilation varied with each organism. Of the three, isolate “Y” was the most proficient, isolate “I” was less, and isolate “II” was the least. For accelerated TNT degradation, addition of glucose or a nitrogenous substance was essential. Complete dissimilation within 24 h by isolate “Y” cultures supplemented with 0.5% yeast extract is presumed since no TNT was detectable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1991
1991
1999
1999

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…Osmon and Klausmeier (2) reported that TNT degradation occurred only in the presence of supplemental organic material and concluded that TNT degradation was co-metabolic. Similarly, TNT degradation by Pseudomonas-Mke organisms was enhanced in the presence of glucose or yeast extract (15). In contrast, others have reported microbial growth using TNT as the sole carbon source (16).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Osmon and Klausmeier (2) reported that TNT degradation occurred only in the presence of supplemental organic material and concluded that TNT degradation was co-metabolic. Similarly, TNT degradation by Pseudomonas-Mke organisms was enhanced in the presence of glucose or yeast extract (15). In contrast, others have reported microbial growth using TNT as the sole carbon source (16).…”
Section: Resultsmentioning
confidence: 98%
“…Microbial degradation of nitroaromatic compounds has been observed under aerobic and anaerobic conditions (2, 6, 7, 11, [13][14][15][17][18][19][20][21][22][23][24][25][26][27][28]. Aerobic degradation of 2,4dinitrotoluene, 2-nitrotoluene, 3-nitrotoluene, and 4-nitrotoluene via oxidative pathways has been described for environmental isolates of Pseudomonas sp.…”
Section: The Maximum Mineralization In Microcosmsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reductive transforma-tion of TNT to aromatic amines has been the strategy of most remediation schemes. Although TNT has been shown to be toxic (15) and is a suspected mutagen (16), the resulting (nitro)aromatic amine transformation products can be highly reactive and may constitute an even greater environmental concern than TNT itself (17). Therefore, the ultimate environmental fate of TNT, in both natural and engineered systems, depends not only on the behavior of TNT, but also on the fate of the reduced aromatic amines.…”
Section: Introductionmentioning
confidence: 99%